Charge-exchange soft X-ray emission of highly charged ions with inclusion of multiple-electron capture. Issue 2 (13th September 2021) - Liang, G Y; Zhu, X L; Wei, H G; Yuan, D W; Zhong, J Y; Wu, Y; Hutton, R; Cui, W; Ma, X W; Zhao, G
ABSTRACT: Charge exchange has been recognized as a primary source of soft X-ray emission in many astrophysical outflow environments, including cometary and planetary exospheres impacted by the solar wind. Some models have been set up by using different data collections of charge-exchange cross-sections. However, multiple-electron transfer has not been included in these models. In this paper, we set up a charge-exchange model with the inclusion of double-electron capture (DEC), and make a detailed investigation of this process on X-ray emissions of highly charged carbon, nitrogen, oxygen, and neon ions by using available experimental cross-sections. We also study the effect of different n- selective cross-sections on soft X-ray emission by using available experimental n -distributions. This work reveals that DEC enhancement on line intensity is linearly proportional to the ratio of ion abundance in the solar wind. It is more obvious for soft X-rays from carbon ions (C 4+ ) in collision with CO2, and the enhancement on line intensity can be up to 53 per cent with typical ion abundances [ Advanced Composition Explorer ( ACE )] in the solar wind. The synthetic spectra with parameters from the Ulysses mission for the solar wind reveal velocity dependence, target dependence, as well as the non-negligible contribution from the DEC.